RECRUITMENT, SELECTION AND TRAINING ON EMPLOYEE PERFORMANCE: - Meidiaputri, Riza Dwi; Sopiah, Sopiah; Syihabudhin, Syihabudhin (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to understand the influence of recruitment, selection, and training on employee performance. The method used in this study is a systematic literature review, where the author collects data from various related articles. The main focus of the study is to explore how these three aspects contribute to employee performance and provide in-depth insights into recruitment, selection, and training practices. The results of the study indicate that many companies still implement recruitment, selection, and training systems that are not fully mature. Therefore, companies must pay more attention to and develop these systems. With good implementation, it is expected to improve overall employee performance, which in turn will benefit the company. Keywords: Management Human Resource; Recruitment; Selection; Training; Employee Performance